2005
DOI: 10.1002/jbm.a.30480
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined cyclic mechanical stretching and microgrooved surface topography on the behavior of fibroblasts

Abstract: Under the influence of mechanical stress, cultured fibroblasts have a tendency to orient themselves perpendicular to the stress direction. Similar cell alignment can be induced by guiding cells along topographical clues, like microgrooves. The aim of this study was to evaluate cell behavior on microgrooved substrates, exposed to cyclic stretching. We hypothesized that cellular shape is mainly determined by topographical clues. On basis of earlier studies, a 10-microm wide square groove, and a 40-microm wide V-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 52 publications
6
48
1
Order By: Relevance
“…The interaction between forces however remains poorly understood [Wang et al, 2003;Loesberg et al, 2005]. Therefore, the two aforementioned parameters, topography and (hyper)gravity, will be investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between forces however remains poorly understood [Wang et al, 2003;Loesberg et al, 2005]. Therefore, the two aforementioned parameters, topography and (hyper)gravity, will be investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a number of investigators have shown that the organization of most anchorage dependent cells may be impacted by principles of contact guidance, in which cells orient themselves in alignment with topographical cues from the substrate or other neighboring cells 23,33 . It has also been demonstrated that mechanical loading constraints can be used to guide cell and matrix alignment 2,13,14,21 . However, in most cases the loading and topographical cues are concomitant factors that act synergistically.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained cell alignment data from 8 studies that plated cells on substrates with micro-ridges of varying height and pitch (Clark et al, 1990;Sutherland et al, 2005;Loesberg et al, 2005Kim et al, 2009;Pot et al, 2010;Sun et al, 2010;. The axis of cell alignment (mean angle) was parallel to the axis of ridge alignment.…”
Section: Structural Guidance Cuementioning
confidence: 99%
“…Cells were either exposed to cyclic uniaxial stretch (Wang & Grood, 2000;Neidlinger-Wilke et al, 2001;Loesberg et al, 2005;Kaunas & Hsu, 2009) or plated on substrates etched with arrays of parallel micro-ridges (Clark et al, 1990;Sutherland et al, 2005;Kim et al, 2009;Pot et al, 2010;Sun et al, 2010). A handful of studies measured the alignment of cells plated on micro-ridged substrates and subjected to cyclic uniaxial stretch (Wang & Grood, 2000;Wang et al, 2004Wang et al, , 2005Loesberg et al, 2005), but only one of these studies examined a range of conditions sufficient for useful analysis . Due to the scarcity of studies that reported sufficiently quantitative data, we included data for any cell type.…”
Section: Cell Alignmentmentioning
confidence: 99%
See 1 more Smart Citation